Rent-sharing no setor industrial brasileiro: uma análise empírica para o período de 2002 – 2012 - Decarli, Aline Saules (2016)
This work analyzes the existence of rent-sharing in the Brazilian industrial sector between the years of 2002 and 2012. This subject has been widely discussed by the international literature, where it is possible to identify evidence supporting the existence of rent-sharing in developed economies. However, considering the Brazilian economy this subject has been little explored and the last empirical studies are limited to the early days of the 90s and 2000s, a period represented by high volatility in the Brazilian economy and also in the labor market. Furthermore, we are not aware of the existence of empirical studies on the subject in the most recent years. In order to empirically examine the relationship between firms' profits and the remuneration of their employees two models were estimated. First, a model in cross section using a detailed individual-level matched data from RAIS and PIA. We also examined whether this correlation occurs evenly between the many level skill from workers. Then the estimate in dynamic panel was held, where the level of aggregation is the industrial sector, we also provided for the correction to the classical endogeneity problem between profits and wages through the use of instrumental variables. The result indicates that an increase in firms' profitability level results in the long run, a rise in wages paid by that sector, but the magnitude of this effect is negligible.